2013
DOI: 10.1073/pnas.1214434110
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse electrical recordings of single neurons from the mouse neocortex

Abstract: The ability of the brain to adapt to environmental demands implies that neurons can change throughout life. The extent to which single neurons actually change remains largely unstudied, however. To evaluate how functional properties of single neurons change over time, we devised a way to perform in vivo time-lapse electrophysiological recordings from the exact same neuron. We monitored the contralateral and ipsilateral sensory-evoked spiking activity of individual L2/3 neurons from the somatosensory cortex of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…While levels of fosGFP are likely to change over the lifetime of a mouse, recent studies show that firing rates in individual cortical neurons can be stable over weeks (Cohen et al, 2013;Margolis et al, 2012). Therefore, fosGFP + neurons could be a stable population of neurons that overlaps with multi-whisker-responsive cortical neurons identified using other techniques (Estebanez et al, 2012;Ghazanfar and Nicolelis, 1997;Sato and Svoboda, 2010).…”
Section: Are Fosgfp + Neurons a Stable Subpopulation Of Cortical Excimentioning
confidence: 94%
“…While levels of fosGFP are likely to change over the lifetime of a mouse, recent studies show that firing rates in individual cortical neurons can be stable over weeks (Cohen et al, 2013;Margolis et al, 2012). Therefore, fosGFP + neurons could be a stable population of neurons that overlaps with multi-whisker-responsive cortical neurons identified using other techniques (Estebanez et al, 2012;Ghazanfar and Nicolelis, 1997;Sato and Svoboda, 2010).…”
Section: Are Fosgfp + Neurons a Stable Subpopulation Of Cortical Excimentioning
confidence: 94%
“…[17,18]). Only recent years have seen a prominent increase in the number of mostly imaging studies addressing the stability and plasticity of neuronal representations in the visual system [15,19,35,36,38,41,43,44,46], barrel cortex [14,29,39,47,60] and auditory cortex [42]. …”
Section: Stability Versus Variability In Sensory Cortexmentioning
confidence: 99%
“…Later studies, however, showed less variable evoked activity in slightly different paradigms. Using single-cell electrophysiological recordings, preference for ipsi- or contralateral whisker stimulation was shown to be stable over 14 days in the small number of cells tested [60]. While confirming a certain degree of session-to-session variability, later Ca 2+ imaging data also showed that some representations in S1 are largely drift-free because the performance of a population decoder of whisker deflection frequency did not progressively decline when trained on an early session and applied to later sessions [47].…”
Section: Stability Versus Variability In Sensory Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased spiking (Fig. 4a2) was observed in this cell post-electroporation25262833. After a 4-day expression, we successfully recovered this neuron's pyramidal morphology at matching location and depth.…”
Section: Resultsmentioning
confidence: 67%